2013
DOI: 10.1016/s1836-9553(13)70161-9
|View full text |Cite
|
Sign up to set email alerts
|

The Berg Balance Scale has high intra- and inter-rater reliability but absolute reliability varies across the scale: a systematic review

Abstract: The Berg Balance Scale has acceptable reliability, although it might not detect modest, clinically important changes in balance in individual subjects. The review was only able to comment on the absolute reliability of the Berg Balance Scale among people with moderately poor to normal balance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
127
0
3

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 218 publications
(135 citation statements)
references
References 17 publications
5
127
0
3
Order By: Relevance
“…The BBS is recommended for use in both research and clinical practice in MS [36] and is considered reliable [37] and valid [38]. In samples of individuals with MS similar to this study, a minimal detectable change (MDC) of 2–4 points has been suggested [3941]. To our knowledge, minimal clinically important difference (MCID) is not known for ambulatory people with MS.…”
Section: Methodsmentioning
confidence: 91%
“…The BBS is recommended for use in both research and clinical practice in MS [36] and is considered reliable [37] and valid [38]. In samples of individuals with MS similar to this study, a minimal detectable change (MDC) of 2–4 points has been suggested [3941]. To our knowledge, minimal clinically important difference (MCID) is not known for ambulatory people with MS.…”
Section: Methodsmentioning
confidence: 91%
“…It could be argued that the change scores demonstrated in the yoga participants may constitute clinically valuable change. A recent systematic review (Downes et al, 2013) suggests that if an individual experiences a change of between 3 and 7 points one can be 95% confident that there has been a real change in balance. Given the improvement in average score of 3.2 points following 14 weeks of yoga, this positive finding warrants further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…This occurs in groups that present a low level of variability, making the scale ineffective to discriminate individuals with balance impairments (17). Moreover, Kornetti et al (18) pointed out that some items of the scale are underused, and many of them do not distinguish people with different skills.…”
Section: Resultsmentioning
confidence: 99%